Intercultural sensitivity of primary school teachers - Popović Kristijan B. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2019)
In a time of mass migration processes, a multitude of cultures, languages and peoples is rapidly striving for a community, which is why interculturalism becomes one of the guiding principles in education. It is inevitable to prepare schools and teachers for cultural, ethnic, linguistic and religious diversity based on the intercultural perspective of a democratic society. By creating interculturally sensitive schools, we can ensure the communication and interaction of the culturally different. The aim of this research was to identify the factors that determine the intercultural sensitivity of primary school teachers, and to identify statistically significant differences in the identified factors in relation to the socio-pedagogical characteristics of teachers. Using a scaler and a factor analysis procedure in a sample of 262 teachers, intercultural sensitivity factors were identified, and statistically significant differences were identified in relation to the socio-pedagogical characteristics of teachers with a small number of identified factors. The results of this empirical study represent a modest contribution to the constitution of new values of interculturalism, since the basic prerequisite for successful education and education of interculturally competent students is the engagement of a well-trained and culturally sensitive teacher.